2015
DOI: 10.1007/s40865-015-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Race and Justice System Attitude Formation During the Transition to Adulthood

Abstract: Purpose Although attitudes towards the justice system are directly related to crime commission, few studies have examined how these attitudes develop from adolescence through early adulthood. Further, despite knowledge that minority youth experience disproportionate contact with the justice system, it is unknown how legal socialization differs by racial group. This study investigates how attitudes towards the justice system develop as youth transition into adulthood, examines how personal experiences with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 54 publications
(53 reference statements)
8
82
0
4
Order By: Relevance
“…Second, are there differences by race? Consistent with prior work showing that racial/ethnic minorities are disproportionately affected by negative policing and justice system practices (see Fine & Cauffman, 2015;Peck, 2015;Weitzer & Tuch, 2006), we expect Black and Latinx youth will perceive legal authorities more negatively than White youth. Further, given racial/ethnic disparities in school punishment (Banks & Banks, 2010;Bennett & Harris, 1982;Mizel et al, 2016;Rios, 2017) that verge on criminalizing misbehavior in ways that parallel law enforcement and the justice system practices (see Kupchik, 2010;Rios, 2017;Welch & Payne, 2018), we expect that for youth of color, perceptions of schools will load onto their perceptions of legal authorities.…”
Section: The Present Studysupporting
confidence: 80%
“…Second, are there differences by race? Consistent with prior work showing that racial/ethnic minorities are disproportionately affected by negative policing and justice system practices (see Fine & Cauffman, 2015;Peck, 2015;Weitzer & Tuch, 2006), we expect Black and Latinx youth will perceive legal authorities more negatively than White youth. Further, given racial/ethnic disparities in school punishment (Banks & Banks, 2010;Bennett & Harris, 1982;Mizel et al, 2016;Rios, 2017) that verge on criminalizing misbehavior in ways that parallel law enforcement and the justice system practices (see Kupchik, 2010;Rios, 2017;Welch & Payne, 2018), we expect that for youth of color, perceptions of schools will load onto their perceptions of legal authorities.…”
Section: The Present Studysupporting
confidence: 80%
“…Given the potential importance of legal attitudes as risk factors for criminal and violent outcomes, researchers are increasingly interested in understanding how these attitudes develop over the life course (Fagan & Tyler, ; McLean, Wolfe, & Pratt, ; Tyler & Trinkner, ). Existing research findings indicate that legal attitudes, and in particular legal cynicism, are moderately stable but still changeable during adolescence and early adulthood (Fine & Cauffman, ; Nivette et al., ; Schuck, ; Stewart, Morris, & Weir, ). Few longitudinal studies, however, have been focused specifically on legal cynicism, and those that have distinguished between legal cynicism and police legitimacy have reported meaningful differences in the patterns and sources of change between outcomes (e.g., Fagan & Piquero, ; Fine & Cauffman, ; Kaiser & Reisig, ).…”
mentioning
confidence: 99%
“…The concept of legal cynicism refers to “the sense in which laws or rules are not considered binding” (Sampson & Bartusch, , p. 786), and it is used to measure the “degree to which individuals feel that the law does not apply to them” (Fine & Cauffman, , p. 345; see also Gifford & Reisig, ; Nivette et al., ). Legal cynicism is conceptually and empirically distinct from the related constructs of obligation to obey the law and “cynicism about the law” (Johnson, Maguire, & Kuhns, ).…”
mentioning
confidence: 99%
“…Compared to younger stages of development, adolescents can comprehend and develop a richer and more abstract understanding of authority (Adelson, Green, & O'Neil, ), often in part by rebelling against and testing its limits (Casey, ). Research has suggested that while increasingly negative perceptions of the legitimacy of legal actors emerge across adolescence, positive and procedurally just encounters can serve as a buoy against that downward trajectory (Fagan & Tyler, ; Fine & Cauffman, ). Given the prevalence and importance of interactions with authority at this stage, a focus on the quality of those contacts and not just their outcomes is warranted.…”
Section: Part 1 a Procedural Justice Framework For Juvenile Justicementioning
confidence: 99%